Solving Stance Detection on Tweets as Multi-Domain and Multi-Task Text Classification - Limin Wang (IEEE, 2021)
Stance detection on tweets aims at classifying the attitude of tweets towards given targets. Existing work leverage attention-based models to learn target-aware stance representations. While those methods achieve substantial success, most of them usually train a model for each target separately despite the scarcity of annotated data for each target. To alleviate limitation of annotated data, some methods turn to external linguistic resources, additional sentiment annotations or target-aware data augmentation techniques for better detection results. We argue that the sharedness of stance-related features across targets in the existing stance detection dataset is not fully exploited. However, directly training on mixed examples of all targets may confuse the model in learning best features for each target. To this end, we borrow the idea from transfer learning and multi-task learning, and formulate stance detection on tweets as a multi-domain multi-task classification problem. We apply the target adversarial learning to capture stance-related features shared by all targets and target descriptors for learning stance-informative features correlating to specific targets. Experimental results on the benchmark SemEval 2016 dataset demonstrate the effectiveness of our model, which outperforms BERT model by over 2% on macro average F1 and achieves superior performance than many recent methods utilizing external resources. We further provide detailed analyses to illustrate the superiority of fully utilizing features shared by different targets.